Effect of gold nanoparticles on extracellular nutrient-cycling enzyme activity and bacterial community in soil slurries: role of nanoparticle size and surface coating. Issue 4 (3rd March 2017) - Asadishad, Bahareh; Chahal, Shawninder; Cianciarelli, Vanessa; Zhou, Kevin; Tufenkji, Nathalie
Abstract : Engineered nanoparticles such as gold that are considered to be relatively chemically inert can influence soil enzyme activities and the composition of microbial communities that play an important role in nutrient cycling and soil health. Abstract : Engineered nanoparticles (ENPs) are introduced to the soil environment mainly via wastewater biosolids applied to soils and their targeted delivery in agricultural applications. The impact of ENP size and surface coating on the activity of extracellular enzymes and bacterial community composition of an agricultural soil was examined using model gold nanoparticles (nAu). These endpoints were chosen as indicators of the soil's response to external disturbances. The activity of five extracellular enzymes important in nutrient-cycling was measured in soils treated with commercially available 50 nm citrate-coated nAu and polyvinylpyrrolidone (PVP)-coated nAu of three different nominal diameters: 5, 50, and 100 nm. At low particle concentration (0.1 mg nAu kg −1 soil), decreasing the size of PVP-nAu resulted in an increased stimulation of soil enzyme activity. No correlation between size of PVP-nAu and soil enzyme activity was observed at a higher dose (100 mg nAu kg −1 soil). At a fixed size of 50 nm, citrate-coated nAu generally resulted in significant increases in soil enzyme activity at 30 days of exposure compared to PVP-coated nAu. Data from 16S rRNA gene sequencing showed that the community composition of soil spiked with citrate-coated nAu clustered significantly away from soil spiked with PVP-nAu at higher concentration (100 mg nAu kg −1 soil), showing the effect of type of nAu surface coatings. Abundance of bacteria annotated to operational taxonomic units (OTUs) from important soil bacterial groups, including Actinobacteria and Proteobacteria, increased following exposure of soil to nAu and more substantially following exposure to citrate-coated nAu for 30 days. This study shows that release of nanomaterials such as nAu to soils may have significant effects on soil enzyme activities and microbial communities and thus impact nutrient cycling in soils. Moreover, this study provides baseline knowledge that may be useful in customizing nanoparticle size and surface coating for their potential use as nutrient delivery agents in agriculture.